2019
DOI: 10.1002/jlcr.3732
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐tuning of the automated [18F]PSMA‐1007 radiosynthesis

Abstract: Radiolabeled prostate‐specific membrane antigen (PSMA) targeting PET‐tracers have become desirable radiopharmaceuticals for the imaging of prostate cancer (PC). Recently, the PET radiotracer [18F]PSMA‐1007 was introduced as an alternative to [68Ga]Ga‐PSMA‐11, for staging and diagnosing biochemically recurrent PC. We incorporated a one‐step procedure for [18F]PSMA‐1007 radiosynthesis, using both Synthra RNplus and GE TRACERlab FxFN automated modules, in accordance with the recently described radiolabeling proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…18 F-PSMA-1007. The 18 F-PSMA-1007 was synthesized by a fully automated process as was previously described (22). In brief, after trapping the ( 18 F)/H 2 18 O from the target, it was loaded onto an anion exchange column (30PS-HCO3; Macherey Nagel), eluted using 0.65 mL of thiobarbituric acid solution (0.075 M; ABX GmBH), and transferred to the reactor followed by addition of 1.5 mL of acetonitrile (Across Organics) and azeotropic removal of water.…”
mentioning
confidence: 99%
“…18 F-PSMA-1007. The 18 F-PSMA-1007 was synthesized by a fully automated process as was previously described (22). In brief, after trapping the ( 18 F)/H 2 18 O from the target, it was loaded onto an anion exchange column (30PS-HCO3; Macherey Nagel), eluted using 0.65 mL of thiobarbituric acid solution (0.075 M; ABX GmBH), and transferred to the reactor followed by addition of 1.5 mL of acetonitrile (Across Organics) and azeotropic removal of water.…”
mentioning
confidence: 99%
“…Radiosynthesis of [ 18 F]-PSMA-1007 were performed using a fully automated radiosynthesizer (AllInOne 36, Trasis, Belgium; with 36 manifold actuators and a disposable uid pathway) as was previously described (Shammi O., et al 2019). The use of disposable cassettes ensures clean and reproducible operations throughout the whole radiolabeling.…”
Section: Methodsmentioning
confidence: 99%
“…For each radiosynthesis a large amount of [ 18 F]-labeled PSMA may be produced, enabling to study a higher number of patients than those with of [ 68 Ga]-PSMA. The [ 18 F] physical half-life (T 1/2 = 109') and larger productions by cyclotron might allow also to provide the distribution to several PET centers distant not more than 4-hours from the producing cyclotron/radiopharmacy facility (Shammi O., et al 2019). Preliminary clinical reports indicated that uorinated PSMA offers other, additional, advantages: higher tumor-to-background ratios (Kesch C. et al, 2017) and low renal excretion (Giesel FL, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The automated, one-step synthesis of [ 18 F]PSMA-1007 was carried out as previously reported (15). Mean radiochemical purity at the end of synthesis was 96.2 ± 1.6% (range 94.1%-99.4%), with no detectable 18 F-fluoride in 13/14 syntheses and 1.1% 18 F − in one synthesis.…”
Section: Radiosynthesismentioning
confidence: 99%